Interdisciplinarity, Multimodality and ICT in the Design of Literary Constellations for Reading Education - José Rovira-Collado; Mónica Ruiz Bañuls; Isabel María Gómez-Trigueros (Universidad Autónoma de Baja California, 2022)
Improving trainee teachers' digital and literary competence by designing multimodal constellations is the key objective of this research. The structured observation of this teaching intervention and the questionnaires administered for analysis (n = 138) offer relevant data that validate the value of this practice for future teachers. Following a cross-sectional descriptive approach, this research employs measures of central tendency (means and standard deviations) and bivariate analyses (Student's t tests) with two mixed questionnaires. The internal consistency of the instruments used (α = .737) confirms their rigor as a tool for analysis. The results obtained show that including multimodal constellations in the classroom as a reading practice improves the teaching and learning of essential skills in teacher training.